2013
DOI: 10.3390/ijms140611915
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effects of a Synthesized Novel 4-Aminoantipyrine Derivative on the Corrosion of Mild Steel in Hydrochloric Acid Solution together with Quantum Chemical Studies

Abstract: 1,5-Dimethyl-4-((2-methylbenzylidene)amino)-2-phenyl-1H-pyrazol-3(2H)-one (DMPO) was synthesized to be evaluated as a corrosion inhibitor. The corrosion inhibitory effects of DMPO on mild steel in 1.0 M HCl were investigated using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, open circuit potential (OCP) and electrochemical frequency modulation (EFM). The results showed that DMPO inhibited mild steel corrosion in acid solution and indicated that the inhibition efficiency increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 46 publications
1
43
0
2
Order By: Relevance
“…Furthermore, DFT is considered a very useful technique to analyse the experimental data, thus in the present investigation, the quantum chemical has been calculated by using density functional theory for explaining the experimental results obtained and to further give insight into the inhibitors action of compounds A1 and A2 on the mild steel surface [52,53]. On the other hand, the quantum chemical results show ability of molecular structure for donation and back donation between the molecule and the metal surface [3].…”
Section: Quantum Chemistry Methodologymentioning
confidence: 99%
“…Furthermore, DFT is considered a very useful technique to analyse the experimental data, thus in the present investigation, the quantum chemical has been calculated by using density functional theory for explaining the experimental results obtained and to further give insight into the inhibitors action of compounds A1 and A2 on the mild steel surface [52,53]. On the other hand, the quantum chemical results show ability of molecular structure for donation and back donation between the molecule and the metal surface [3].…”
Section: Quantum Chemistry Methodologymentioning
confidence: 99%
“…The inhibitor may affect either the anodic or the cathodic reaction, or both. 23 Therefore, CA and Linalool inhibit cathodic hydrogen evolution and anodic metal dissolution reactions. Since the anodic and cathodic Tafel lines slopes β a and β c of CA and Linalool were found to change slightly with inhibitor concentration, this indicates that CA leaf extract and Linalool inhibit the corrosion of mild steel surface through similar mechanism.…”
Section: Spectrophotometric Analysismentioning
confidence: 99%
“…As per the application assets of the field various measures are guessed using theoretical field. Recently Ahmad et al 105 reported inhibition effects of a synthesized novel 4-aminoantipyrine derivative on the corrosion of mild steel in hydrochloric acid solution together with quantum chemical studies, electronic properties such as highest occupied molecular orbital energy (HOMO), lowest unoccupied molecular orbital energy (LUMO) and dipole moment (μ) were calculated and discussed. The results showed that the corrosion inhibition efficiency increased with an increase in the HOMO values but with a decrease in the LUMO value.…”
Section: Coordination Complexes With Tetradentate Bases/mixed Ligandsmentioning
confidence: 99%